Globalization Enables Telkom Indonesia to be Interconnected with International Telecommunications Networks, Supporting Seamless Communication and Data Exchange Across Border - Khan, Muhammad Asif (MultiTech Publisher, 2023)
This case study delves into the globalization journey of Telkom Indonesia, a leading telecommunications company in Southeast Asia. The case study explores Telkom Indonesia's motivations for embracing globalization, the challenges encountered, and the resultant impact on the company's growth and global connectivity. It then delves into the company's decision to venture beyond national borders, exploring the drivers behind its international expansion, such as seeking new growth opportunities, accessing untapped markets, and diversifying revenue streams. It also assesses how Telkom Indonesia's interconnected telecommunications networks support seamless communication and data exchange across borders, enabling the company to serve an increasingly diverse and global customer base. Challenges faced during the globalization process are explored, including regulatory complexities, cultural differences, and competition from international telecom giants. The study highlights the importance of cultural sensitivity and adaptability as Telkom Indonesia navigates varying legal environments and customer preferences in international markets. The study evaluates the company's approach to tailoring services and solutions to meet the unique needs and demands of different global markets and emphasizes the transformative impact of globalization on Telkom Indonesia's growth and global connectivity.